Is the time interval between HCG administration and oocyte retrieval associated with oocyte retrieval rate?. Issue 5 (November 2015) - Bosdou, Julia K.; Kolibianakis, Efstratios M.; Venetis, Christos A.; Zepiridis, Leonidas; Chatzimeletiou, Katerina; Makedos, Anastasios; Triantafyllidis, Stylianos; Masouridou, Sevasti; Mitsoli, Anna; Tarlatzis, Basil
Abstract: The aim of this study was to evaluate whether prolongation of the time interval between HCG administration and oocyte retrieval, from 36 h to 38 h, affects oocyte retrieval rate in women undergoing ovarian stimulation with gonadotrophins and GnRH antagonists for IVF. One hundred and fifty-six normo-ovulatory women were randomized to have oocyte retrieval performed 36 h ( n = 78) or 38 h ( n = 78) following HCG administration. Oocyte retrieval rate was defined as number of cumulus–oocyte–complex (COC) retrieved/follicle ≥11 mm present on day of HCG administration. No significant differences were observed between the groups regarding baseline characteristics. Moreover, no significant difference was observed between the groups regarding oocyte retrieval rate (difference: + 1.2%, 95% CI for difference between medians: −4.5 to +12.1). The median (95% CI for the median) was not significantly different between the groups regarding number of cumulus-oocyte-complexes (COCs) retrieved: 5.5 (5.0–7.0) versus 6.0 (5.0–6.2), respectively, and fertilization rates: 57.7% (50.0–66.7) versus 50.0% (44.8–65.5), respectively. Live birth rates were similar between the groups (20.5% versus 16.7%, RD: + 3.8%, 95% CI: −8.5 to +16.1, respectively). Prolongation of time interval between HCG administration and oocyte retrieval from 36 h to 38 h does not affect oocyte retrieval rate.